PENGARUH KONSELING APOTEKER TERHADAP KEPATUHAN TERAPI PASIEN DIABETES MELITUS DI BEBERAPA PUSKESMAS DAN RUMAH SAKIT - Putri, Mareta Ananda; Sukandar, Elin Yulinah (Jurnal Buana Farma, 2024)
Diabetes mellitus is a global health issue that requires a comprehensive management approach. Pharmacist interventions have proven effective in enhancing patient adherence to medication and improving clinical outcomes. This study aims to systematically review pharmacist interventions for diabetes mellitus patients and their impact on medication adherence and glycemic control. The research method used was a narrative literature review, analyzing 188 articles from PubMed and 200 articles from Google Scholar, with 20 studies meeting the inclusion criteria, including 12 studies conducted in community health centers (puskesmas) and 8 studies in hospitals. The findings indicate that pharmacist counseling interventions significantly improve medication adherence and lower HbA1c levels. In community health centers, adherence increased from 9.2% to 61%, and HbA1c decreased from 8.5% to 7.2%. In hospitals, the average HbA1c reduction was between 1.5% and 2%. The multifaceted counseling approach was more effective compared to telephone counseling, which showed an HbA1c reduction of 0.3%. These findings highlight the critical role of pharmacists in managing type 2 diabetes mellitus.